“DICTIONARY TYPES AND DICTIONARY USERS” (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This exploration of “Dictionary Types and Dictionary Users” delves into the diverse categories of dictionaries available and the variousaudiences that utilize them. It categorizes dictionaries into general, specialized, bilingual multilingual, thesauruses, etymological dictionaries, visual dictionaries, and digital resources